A novel platform for engineering blood‐brain barrier‐crossing bispecific biologics. Issue 11 (28th July 2014) - Farrington, Graham K.; Caram‐Salas, Nadia; Haqqani, Arsalan S.; Brunette, Eric; Eldredge, John; Pepinsky, Blake; Antognetti, Giovanna; Baumann, Ewa; Ding, Wen; Garber, Ellen; Jiang, Susan; Delaney, Christie; et al.
Abstract : The blood‐brain barrier (BBB) prevents the access of therapeutic antibodies to central nervous system (CNS) targets. The engineering of bispecific antibodies in which a therapeutic "arm" is combined with a BBB‐transcytosing arm can significantly enhance their brain delivery. The BBB‐permeable single‐domain antibody FC5 was previously isolated by phenotypic panning of a naive llama single‐domain antibody phage display library. In this study, FC5 was engineered as a mono‐ and bivalent fusion with the human Fc domain to optimize it as a modular brain delivery platform. In vitro studies demonstrated that the bivalent fusion of FC5 with Fc increased the rate of transcytosis ( P app ) across brain endothelial monolayer by 25% compared with monovalent fusion. Up to a 30‐fold enhanced apparent brain exposure (derived from serum and cerebrospinal fluid pharmacokinetic profiles) of FC5‐compared with control domain antibody‐Fc fusions after systemic dosing in rats was observed. Systemic pharmacological potency was evaluated in the Hargreaves model of inflammatory pain using the BBB‐impermeable neuropeptides dalargin and neuropeptide Y chemically conjugated with FC5‐Fc fusion proteins. Improved serum pharmacokinetics of Fc‐fused FC5 contributed to a 60‐fold increase in pharmacological potency compared with the single‐domain version of FC5; bivalent and monovalent FC5 fusions with Fc exhibited similar systemic pharmacological potency. The study demonstrates that modular incorporation of FC5 as the BBB‐carrier arm in bispecific antibodies or antibody‐drug conjugates offers an avenue to develop pharmacologically active biotherapeutics for CNS indications.—Farrington, G. K., Caram‐Salas, N., Haqqani, A. S., Brunette, E., Eldredge, J., Pepinsky, B., Antognetti, G., Baumann, E., Ding, W., Garber, E., Jiang, S., Delaney, C., Boileau, E., Sisk, W. P., Stanimirovic, D. B., A novel platform for engineering blood‐brain barrier‐crossing bispecific biologics. FASEB J. 28, 4764–4778 (2014). www.fasebj.org